Quantum effects in the radial thermal expansion of bundles of single-walled carbon nanotubes doped with ⁴He - Dolbin, A.V.; Esel'son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Popov, S.N. (Физика низких температур, 2010)
The radial thermal expansion αr of bundles of single-walled carbon nanotubes saturated with ⁴He impurities to the molar concentration 9.4% has been investigated in the interval 2.5–9.5 K using the dilatometric method. In the interval 2.1–3.7 K α r is negative and is several times higher than the negative αr for pure nanotube bundles. This most likely points to ⁴He atom tunneling between different positions in the nanotube bundle system. The excess expansion was reduced with decreasing ⁴He concentration.